2017
DOI: 10.1002/acm2.12189
|View full text |Cite
|
Sign up to set email alerts
|

Potential proton and photon dose degradation in advanced head and neck cancer patients by intratherapy changes

Abstract: PurposeEvaluation of dose degradation by anatomic changes for head‐and‐neck cancer (HNC) intensity‐modulated proton therapy (IMPT) relative to intensity‐modulated photon therapy (IMRT) and identification of potential indicators for IMPT treatment plan adaptation.MethodsFor 31 advanced HNC datasets, IMPT and IMRT plans were recalculated on a computed tomography scan (CT) taken after about 4 weeks of therapy. Dose parameter changes were determined for the organs at risk (OARs) spinal cord, brain stem, parotid gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…Blanchard et al have recently shown in their facility that IMPT can lead to reduce reliance on feeding tubes and weight loss at a median time point of 32 months post radiotherapy. Similarly, IMPT can reduce the radiation dose to the healthy surrounding tissue including DARS . In the case of IMPT, there may be a higher requirement of replanning as a result of anatomical changes in a similar way to the methodology described in Berwouts et al…”
Section: Discussionmentioning
confidence: 99%
“…Blanchard et al have recently shown in their facility that IMPT can lead to reduce reliance on feeding tubes and weight loss at a median time point of 32 months post radiotherapy. Similarly, IMPT can reduce the radiation dose to the healthy surrounding tissue including DARS . In the case of IMPT, there may be a higher requirement of replanning as a result of anatomical changes in a similar way to the methodology described in Berwouts et al…”
Section: Discussionmentioning
confidence: 99%
“…How can you fully realize the potential of these technologies without ART? For example, proton therapy distributions are much less robust than photon therapy in the presence of anatomical variation . The clinical viability of a technology such as the MR‐LINAC is completely dependent on the ability to adapt plans when anatomical changes are seen .…”
Section: Rebuttalmentioning
confidence: 99%
“…The issue of standardising CTV delineation is as relevant with IMPT, notwithstanding the unique treatment planning aspects for IMPT target volumes which cannot be based on geometric margin expansion alone, owing to increased range uncertainty with resultant increased sensitivity to set-up and anatomical changes. Degradation of the dose distribution for both the target volumes and OARs can be proportionately worse for IMPT compared to IMRT over the entire course of treatment, resulting in less than anticipated therapeutic benefits for IMPT [ 16 , 17 ]. Studies evaluating robust planning parameters specific to oropharyngeal cancer have recently emerged and robustness settings do influence the dose to OARs with possible clinical impact [ 18 , 19 ].…”
Section: Clinical Target Volume Definitionmentioning
confidence: 99%